2020
DOI: 10.1177/0021998319899154
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and thermal properties of nickel-coated carbon fibers/aluminum composites

Abstract: Electroless nickel-coated carbon fibers/aluminum composites were prepared by spark plasma sintering, and the effect of nickel coating on microstructure and thermal properties of the composites has been investigated. Nickel coating on carbon fibers resulted in more homogeneous distributions of carbon fibers in aluminum matrix, higher relative density of carbon fibers/aluminum composites, and stronger interfacial bonding between carbon fibers and aluminum. Microstructural observations exhibited that the majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The result showed that the tensile strength and Vickers hardness increased by 71% and 88%, respectively. Using aluminum alloy as raw material, aluminum alloy matrix was prepared by extrusion casting and spark plasma technology [22,23]. Through experiment and theoretical analysis, the mechanical properties of carbon fiber and aluminum matrix composites at different temperatures, and the mechanical properties of carbon fiber and aluminum matrix composites at different temperatures, were discussed [24].…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that the tensile strength and Vickers hardness increased by 71% and 88%, respectively. Using aluminum alloy as raw material, aluminum alloy matrix was prepared by extrusion casting and spark plasma technology [22,23]. Through experiment and theoretical analysis, the mechanical properties of carbon fiber and aluminum matrix composites at different temperatures, and the mechanical properties of carbon fiber and aluminum matrix composites at different temperatures, were discussed [24].…”
Section: Introductionmentioning
confidence: 99%
“…• [18].This makes it easy to form pores and agglomerations at the interface due to their significant difference in density and melting points [7,19]. The metallic coating is usually applied on the CF surface to improve not only the interfacial bonding and wettability but also the properties of composites [20][21][22]. The electroless coating is the most common technique used in the coating process owing to its simple, few tools used, and uniform coating layers can be obtained [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, many studies have paid attention to the effect of Ni surface modification on CF/Al composites fabricated by solid-state techniques [22,39,40]. Others studied the effect of Cu surface modification on the properties of composites.…”
Section: Introductionmentioning
confidence: 99%